Papua New Guinea : Staff Report for the 2003 Article IV Consultation and Request for an Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report, 2003)
This paper assesses Papua New Guinea's 2003 Article IV Consultation and a Request for an Extension of Repurchase Expectations. Since the mid-1990s, Papua New Guinea's growth performance has been weak and poverty has increased owing to an unfavorable external environment, loose macroeconomic policies, and deep-seated structural impediments to growth. The IMF staff supports the authorities' request to extend their repurchase expectations to the IMF in light of the weakness in Papua New Guinea's balance-of-payments position and the deterioration in key external indicators mainly because of lower mineral exports over the medium term.